Information seeking behaviour of faculty: The case of the College of Science, Kwame Nkrumah University of Science and Technology, Kumasi, Ghana (Journal of Science and Technology, 2016)
The article sought to find the information seeking behaviour of faculty members of the College of Science, Kwame Nkrumah University of Science and Technology, Kumasi, Ghana. The survey method was employed. Questionnaire instrument was used to collect data on method of selectinginformation, type of information sought, purpose for seeking information, types of tools used and problems involved in seeking information. Seventy out of 110 responded. A little over half of the respondents sought information through reviewing articles; close to the same proportionconsulted the Internet; about four out of five of the respondents sought information for doing research work; and over three out of five sought information for preparing lecture notes. Majority of the respondents consulted textbooks for information while half consulted periodicals;and almost all the respondents used Google search engine to access information on the Internet. Sciencedirect and Ebscohost were the most used online journals. The commonest problems faced by respondents were unavailability of information, abstract instead of full-text documentsand very old textbooks in the library. Involvement of faculty members in the selection of textbooks and purchase of full-text documents by the library on behalf of faculty members among others were recommended to address these problems.